2020
DOI: 10.1155/2020/4249067
|View full text |Cite
|
Sign up to set email alerts
|

Occult Thyroid Carcinoma without Malignant Thyroid Gland Findings during Preoperative Examination: Report of Three Cases

Abstract: Occult thyroid carcinoma preceded by clinical manifestations and findings from extrathyroidal tumors is rare. The lack of malignant findings in the thyroid during the preoperative examination makes diagnosis difficult. We encountered a 71-year-old man with a primary ectopic thyroid carcinoma causing superior vena cava syndrome. Although no malignant findings were found in the thyroid gland, biopsy of bone metastases led to the diagnosis of thyroid cancer. HE staining of bone metastases revealed nuclear feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(30 citation statements)
references
References 7 publications
0
30
0
Order By: Relevance
“…Cancers 2024, 16, x FOR PEER REVIEW 37 of 55 and thymectomy in a patient with a prior history of thyroidectomy for cervical thyroid cancer [123]; left hemi-thyroidectomy and isthmectomy plus median sternotomy [129]; partial sternotomy and total thyroidectomy associated with a selective parathyroidectomy via mediastinal and cervical exploration [115].…”
Section: Proposed 10-item Algorithm Of Emt Approachmentioning
confidence: 99%
See 3 more Smart Citations
“…Cancers 2024, 16, x FOR PEER REVIEW 37 of 55 and thymectomy in a patient with a prior history of thyroidectomy for cervical thyroid cancer [123]; left hemi-thyroidectomy and isthmectomy plus median sternotomy [129]; partial sternotomy and total thyroidectomy associated with a selective parathyroidectomy via mediastinal and cervical exploration [115].…”
Section: Proposed 10-item Algorithm Of Emt Approachmentioning
confidence: 99%
“…The longest period of follow-up sinc reported data is up to one to two years [ showed that EMTs remained stable for a that were not removed upon cytological c 1/7 patient had a post-operatory complication: chyle leak & phrenic nerve injury (conservative approach) Gao 2023 [7] Cancers 2024, 16, x FOR PEER REVIEW 37 of 55 and thymectomy in a patient with a prior history of thyroidectomy for cervical thyroid cancer [123]; left hemi-thyroidectomy and isthmectomy plus median sternotomy [129]; partial sternotomy and total thyroidectomy associated with a selective parathyroidectomy via mediastinal and cervical exploration [115].…”
Section: Outcome After Identification Of Emtsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytologic evaluation has a higher speci city but a lower sensitivity, and the combination of FNA-Tg and FNAC examination is widely recommended (43-46, 48, 51). In most cases, noticeably elevated FNA-Tg, even without cytologic evidence, can strongly indicate the existence of lymphatic metastasis (52), and therefore, further thyroidectomy and neck dissection are usually performed. However, false-positive results may lead to misdiagnosis and unnecessary surgery, which can be explained by three main reasons.…”
Section: Diagnosismentioning
confidence: 99%